The new German cinema : music, history, and the matter of style - Flinn, Caryl (University of California Press, 2004)
When New German cinema directors like R.W. Fassbinder, Ulrike Ottinger, and Werner Schroeter explored issues of identity--national, political, personal, and sexual--music and film style played crucial roles. Most studies of the celebrated film movement, however, have sidestepped the role of music, a curious oversight given its importance to German culture and nation formation.